PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA OPERASI HITUNG PECAHAN PADA SISWA KELAS V SD NEGERI 060912 MEDAN DENAI: Penelitian Tindakan Kelas - Annisah Yuliana; Chairunnisa Amelia; Sri Suharni (STKIP Subang, 2024)
This research was motivated by students' low level of activity and very limited understanding of fraction operations, causing students to not be able to equate different denominators. Students' ability to calculate fractional operations, especially operating them, is still very poor for students so that the learning outcomes obtained are still low. Based on the results of initial observations carried out at SDN 060912 Medan Denai, symptoms were found such as: 1) The results of tests on class V students at State Elementary School 060912 Medan Denai obtained facts about the Mathematics learning outcomes of 32 students who apparently reached the KKM set by the school, namely 70. 12 students (39.39%) and those who did not reach the KKM were 20 students (59.4%) with an average score of 67.5. 2) Students tend to get bored when following Mathematics lessons, 3) Students lack curiosity about the lessons taught by the teacher in class, and 4) So far, teachers tend to explain the material, provide example questions and give exercises in a monotonous way. The aim of this research is to increase the activeness and understanding of mathematical learning of arithmetic operations for adding fractions with unlike denominators through the TGT type cooperative learning model in class V students at SDN 060912 Medan Denai. The method used is the classroom action research method (PTK). The research was carried out in 2 cycles, each cycle there were 4 stages, namely planning, implementation, observation and reflection. To improve students' mathematics learning outcomes, the TGT type cooperative learning model is used so that the research results for each cycle show an increase in each cycle. In the first cycle of action the level of student learning outcomes reached 30% and in the second cycle of action the learning outcomes achieved by students were 90% learning completeness and had reached the KKM. Applying the TGT type cooperative learning model can improve student learning outcomes regarding the operation of adding fractions with unequal denominators for class V SDN 060912 Medan Denai.